100 All that glitters is not GARS. Issue 6 (27th May 2022) - Doherty, Carolynne M; Pipis, Menelaos; Skorupinska, Mariola; Manzur, Adnan; Muntoni, Francesco; Shah, Sachit; Morrow, Jasper; Rossor, Alexander M; Reilly, Mary M
Abstract : Background: A 22-year-old woman was initially assessed in the context of a family history of distal wasting and weakness, typically with upper limb onset, then lower limb involvement. When assessed as a child her phenotype was recognised to be atypical compared to her sister, but she was thought to be affected. Ultimately the family was diagnosed with distal hereditary motor neuropathy due to a GARS mutation. However, this patient did not carry the mutation, prompting further evaluation. Case: At age 11 the left foot was smaller with some toe clawing and cavus deformity. Left sided wasting of tibialis anterior and the posterior compartment was seen, ankle dorsiflexors were grade 3. Results: Nerve conduction studies and EMG were normal in the right leg and arms. Chronic denervation was identified in L4, L5 and S1. MRI of lumbar spine was normal. However, 2 areas of marked thickening and enhancement were seen in the left sciatic nerve in the upper thigh and a further lesion in the mid- thigh. Fascicular preservation of the nerve was felt to be strongly suggestive of a perineurioma. Discussion: This case highlights the importance of careful phenotyping when validating novel variants in potentially causative genes. c.doherty@ucl.ac.uk